Actual neighborhood-level crime predicts body mass index z-score changes in a multi-racial/ethnic sample of children - Suminsk, Richard R.; Robson, Shannon M.; May, Linda L.; Blair, Rachel I.; Orsega-Smith, Elizabeth M. (My University, 2018)
Longitudinal studies are warranted to clarify the influence crime has on health outcomes in children especially children representing multiple racial/ethnic backgrounds. To address this need, the current study examined whether neighborhood-level crime predicted changes in body mass index z (BMIz) scores in 373 White (W), 627 African American (AA), 1020 Hispanic (H), and 88 Asian (A), five to ten year-old boys and girls living in urban neighborhoods. Heights and weights were assessed at baseline (2012) and three-years later and used to calculate BMIz scores. Characteristics of zip codes where students lived during the three-year period were obtained at baseline from various sources. The Crime Risk Index (CRI) for each zip code was calculated using actual crime statistics. Multiple linear regression analyses were conducted to examine associations between baseline CRI and follow-up BMIz scores while controlling for other variables including BMIz at baseline. The CRI and BMIz scores differed significantly by race/ethnicity with the highest values for both noted in H. Regression analyses indicated that the CRI accounted for a significant percentage of the variance in follow-up BMIz scores in the overall sample. When race/ethnicity was considered, the CRI predicted follow-up BMIz scores only in W children. The CRI was not significantly associated with BMIz scores in the other races/ethnicities. The impact actual, neighborhood-level crime has on BMI in children is complex. Based on the existing evidence, considering actual crime as a primary target in obesity prevention would be premature especially in racial/ethnicity minority children living in urban areas.
Keywords: Longitudinal study; Public health; Obesity; Safety